Synthesis and Properties of Macrocyclic Butanoic Acid Conjugates as a Promising Delivery Formulation for the Nutrition of Colon - Jingui Cheng; Benpeng Li; Peipei Ma; Mengying Liu; Zhizhong Wang (The Scientific World Journal)
Butanoic acid plays a significant role in the maintenance of mucosal health and is the preferred energy substrate for the cells in the colon. Here, butanoic acid was selectively conjugated to the secondary hydroxyl group of β-cyclodextrin through ester bond using sodium hydride as the deprotonation reagent. The preliminary release behaviors of butanoic acid in rat gastrointestinal tract contents were investigated at 37°C within 12 h. In the contents of stomach, the conjugates did seldom release butanoic acid, released butanoic acid only 5.8% in the contents of small intestine, and released butanoic acid significantly up to 38.4% in the contents of colon. These results indicate that the conjugate activation took place site specifically in the rat colonic contents, via the biodegradation by glycosidases and hydrolases in the colon. Therefore, the β-cyclodextrin conjugates of butanoic acid may be of value as an orally administered colon-specific formulation for the nutrition of colon.